The Effect of Service Quality on the Number of Peristi Patients at Unisma Islamic Hospital Malang - Sari, Dwi Ratna; Widyaningrum, Kurnia; Sarwiyata, Tri Wahyu; Rahmawati, Triwahyuning (Fakultas Kedokteran Universitas Brawijaya)
ABSTRACTHospitals, as the spearhead of health services, are required to provide quality services that meet the expectations of the community. Decreasing number of Obstetrics and Gynecology (Peristi) patients at Unisma Islamic Hospital Malang into 119 patients in June 2019 and low BOR value of 15.1%-46.8% that is below the standard (60-85%) indicated that the number of patient visits to the Peristi unit is low. Low patient visits are associated with the satisfaction of quality services. This study aimed to determine the effect of service quality on the increasing number of patients. This study was carried out by using a survey with a cross-sectional study approach among patients in the obstetric unit and inpatients installation for three months. The sample in this study were 139 respondents from the obstetric unit and 18 respondents from Peristi obtained using the accidental sampling method. Data were collected using questionnaires based on the dimensions of service quality and semi-structured interviews. The results showed a number of respondent statements related to the quality of hospital services including dissatisfaction of outpatient flow which was not as promised, long patient waiting time, less responsive officers in responding to complaints or providing information to patients, and waiting room facilities that are not representative and lack complete equipment to support its services. The hospital is expected to provide high-quality services and excellent service to increase patient satisfaction so that it has an impact on increasing the number of patient visits to the Peristi Unit.